Analisis Pengaruh Leadership Trust dan Leadership Visibility Terhadap Employee Psychological Safety (EPS) Karyawan Perusahaan Target Akuisisi - Rima Febriana; Riani Rachmawati (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
Acquisition is one of the strategic activities for many organizations in order to maintain sustainable competitive advantages. Evidence shows that acquisition failed mostly because of cultural conflict, management style, and value created failures. Prior researches focused on integration process as well as combination process and still result inconsistency findings about post-acquisition performance and employee psychological safety. This research aims to explore and bridge the gap of the acquisition success from human resources side particularly in acquiring leadership style to acquired employee psychological safety (EPS). This study captures employees’ perceive about leadership trust and leadership visibility of acquiring leaders, integration process, and deal status toward their psychological safety post-acquisition as dependent variable. Deal status was known has moderating effect on leadership visibility to EPS. The results show that leadership visibility has no significant effect on EPS while leadership trust positively affects the EPS. When we examine acquisition phase which is represented by integration process and deal status only the integration process has positively significant effect on EPS. Communication quality has the highest positive effect in post-acquisition integration process. Otherwise power differential statistically proved has the highest negative effect on EPS in post-acquisition deal status. Furthermore, there is pure moderating effect resulting from deal status on leadership visibility. Overall, this study contributes to further explanation about what are important skill and behavior that need to be considered for leaders to gain target employees’ psychological safety